Village’s Women Participation in Sustainable Waste Management - Rahmawati, Emma; Sukarno, Taufan Daniarta; Purwanto, Anang Dwi (Soegijapranata Catholic University, 2022)
Sustainable development requires the community’s active involvement, as well as other development inside the village. One of the most crucial dimensions of development in recent years is the environmental issues, especially waste problems, where there is a lot of unhandled waste in rural areas. Fortunately, now there are villages that have succeeded in managing their waste in a sustainable manner with the support of village women's participation. The aim of this study was to determine the participation of village women in sustainable waste management. The research method uses descriptive qualitative data collection through in-depth interviews, Focus Group Discussion (FGD), observation, and documentation. The results showed that the participation of village women in the flow of sustainable waste management has various forms of participation, which contained in each stage activities of management, sorting, transporting, processing, and utilizing the results of waste processing. Factors that encouraged the participation of village women in village waste management development were the community’s own willingness, ability to perform, and the opportunity to be actively involved. The village women proved that they were the largest producers of household waste, but at the same time were the ones that helped solve the waste problem. Through their services to their community, they have also increased the family's economic income through their involvement in waste management.